Vectors of Individual and Organizational Performance Within the Fiscal Administration - AVRĂMESCU, Gabriel Ioan (Journal of Advanced Research in Management, 2020)
To use the full potential of employees, managers need to know what stimulates them to increase their level of performance so that this energy can be channelled adequately to specific results, which add value to the resources consumed in the production process. A motivational work environment is one of the critical forces that stimulate individuals to ensure superior performance. The motivational work environment increases morale, creates professional satisfaction, reduces unnecessary stress, decreases absenteeism, and the organization's rate of abandonment promotes performance. Moreover, managers' supportive behavior is one of the crucial factors in creating a motivational work environment. In the paper, we aim to assess the influences of supportive, performance-oriented management on civil servants' activity and performance in the fiscal administration and the challenges and obstacles managers face in this regard.